Using social media to enrich information systems field trip experiences: Students' satisfaction and continuance intentions. (October 2016) - Kaewkitipong, Laddawan; Chen, Charlie C.; Ractham, Peter
Abstract: A well-designed field trip can promote active learning and reinforce classroom materials. Few studies have examined the potential for social media to enhance IS field trip experiences by promoting active and collaborative learning. One major barrier to the exploitation of this potential is the lack of the adoption of social media by students as a learning tool to enhance field trip experiences. Therefore, the first task is to understand how to increase the satisfaction of students in their use of social media to enhance IS field trips. This research sets out to understand the factors that could help increase students' satisfaction with the use of social media to enhance IS field trips, and thereby their intentions to continue to use social media in future field trips. The results show that to increase user satisfaction, course instructors should ensure that students perceive the social media sites used for enhancing field trip study to be trustworthy, effortless, useful and accepted by their peers. Future research could determine how we can incorporate the use of social media to enhance the field trip learning experience. Highlights: Research on an adoption of social media for field trip study is limited. Students use social media to learn IT products before, during, and after field trip. We report factors affecting students' satisfaction in using social media for field trip. Provided social environment for them to learn, students show intention to continue.